PELECEHAN SEKSUAL SECARA VERBAL DALAM PERSPEKTIF PEMAHAMAN MASYARAKAT - Eka Putri, Sabila; Rahmi, Atikah (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
This study aims to determine the criminal act of verbal sexual harassment from the perspective of the community in the XII hamlet, gg. Mentimun 19, Percut Sei Tuan and students of the Muhammadiyah University of North Sumatra. This study uses an empirical legal method. This study also explains the laws governing the criminal act of verbal sexual harassment with the sanctions received by the perpetrators. In this study, data was obtained that the general public aged 40 years and over considered verbal sexual harassment not a serious matter that must be followed up by law in accordance with applicable laws, while students and people aged 20-30 years considered verbal harassment as a criminal act of harassment that must be followed up with legal sanctions in accordance with applicable laws. One of the factors causing cases of sexual violence is gender inequality in society. Women are often targeted because their position is not equal to men. Thus, gender equality is not only a basic right, but can be the key to changing the dynamics of sexual violence. For this reason, important steps are needed to realize gender equality and justice as an effort to prevent sexual violence.